2020
DOI: 10.7759/cureus.9619
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy in Sickle Cell Disease

Abstract: Sickle cell disease (SCD) is an inherited disorder that occurs due to point mutation in the betaglobin chain resulting in the production of hemoglobin S that tends to become rigid and sickleshaped under low oxygen concentration. These sickle-shaped red blood cells (RBCs) obstruct the blood vessels leading to reduced blood flow to the organs, causing ischemia and tissue fibrosis. These sickle RBCs being abnormal in shape are frequently sequestered by the spleen, creating a state of chronic anemia in the body. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…This concept was supported by our finding that the other component of cardiac output, heart rate, was not a predictor of mortality. It is possible that inability to increase systolic blood pressure during exercise that we observed is related to the development of heart failure with preserved ejection fraction (HFpEF), or right heart dysfunction in the setting of high pulmonary pressures, or a combination of both pathologies 33,34 . Decreased risk of mortality associated with exercise‐induced increases of systolic blood pressure has also been identified in other conditions.…”
Section: Discussionmentioning
confidence: 81%
“…This concept was supported by our finding that the other component of cardiac output, heart rate, was not a predictor of mortality. It is possible that inability to increase systolic blood pressure during exercise that we observed is related to the development of heart failure with preserved ejection fraction (HFpEF), or right heart dysfunction in the setting of high pulmonary pressures, or a combination of both pathologies 33,34 . Decreased risk of mortality associated with exercise‐induced increases of systolic blood pressure has also been identified in other conditions.…”
Section: Discussionmentioning
confidence: 81%
“…In our study, serum ferritin level is an independent risk factor for cardiac hypertrophy, and effective chelation therapy may benefit these patients. However, several studies have shown that myocardial iron overload is not common in patients with SCA [ 6 ]. Therefore, other non-ferrous mechanisms are more responsible for the cardiac geometry changes seen in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…With the renin-angiotensin-aldosterone system (RAAS) activation due to chronic anemia and peripheral vascular dilatation, cardiac remodeling is triggered, and dilatation begins to occur in the left ventricle. This dilatation further triggers compensatory eccentric cardiac hypertrophy [ 6 ]. Conditions such as increased iron load (due to chronic blood transfusion) and pulmonary hypertension associated with decreased nitric oxide also contribute to ventricular hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Within these are hemoglobinopathy including sickle cell disease (SCD), which are caused by a single germ-line mutation substituting (A to T) in the codon for amino acid 6. The change converts a glutamic acid codon (GAG) to a valine codon (GTG) [29,30].…”
Section: Diseases Arising From Mutationsmentioning
confidence: 99%
“…Further, this mutation is thought in part to be responsible for 40-50% of hereditary cases of ALS, and 5-10% of cases without family history. This mutation consists of an expansion of a sequence of hexanucleotide (GGGGCC) DNA bases, going from a few copies (less than 20 in a healthy person) to more than 1000 copies [30]. Until now, it still remains unclear how this GGGGCC base repeat expansions cause neurodegeneration in ALS.…”
Section: Single Mutation As a Lead Cause Of Amyotrophic Lateral Scler...mentioning
confidence: 99%